Implementasi Coretax Bagi UMKM di Kelurahan Benda Baru untuk Meningkatkan Pemahaman Perpajakan Menuju Kepatuhan Pajak Digital - Kurniawan, Budi Santoso; Mardjuki, Vicky Cesar; Muntazar, Fadhil; Wijaya, Dede Satia (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The digital transformation of tax administration through the implementation of the Core Tax Administration System (Coretax) is an essential component of the national tax reform agenda. However, the level of tax literacy and digital readiness among micro, small, and medium enterprises (MSMEs) remains low, potentially hindering tax compliance. This community engagement program aims to enhance the understanding and skills of MSME actors in Benda Baru Subdistrict in using Coretax as the new tax administration system. The methods employed include socialization, technical training, hands-on practice, and structured assistance. The results indicate an improvement in participants’ understanding of MSME tax obligations, the benefits of Coretax, and their basic abilities in performing registration and simulating digital tax reporting. This activity contributes to building a foundation for digital tax compliance and strengthening MSME readiness for modern tax administration systems.